انعكاسات الصدمة النفطية 2014 على أداء أسواق الأوراق المالية الخليجية - بوشول, السعيد; مصباحي, محمد الأمين (جامعة الوادي University of Eloued, 2015)
تهدف الورقة البحثية بعنوان : انعكاسات الصدمة النفطية 2014 على أداء أسواق الأوراق المالية الخليجية، إلى محاولة التعرف تاريخ الصدمات النفطية ،والتي من خلالها نستطيع أن نقارن بين الصدمة النفطية الأخيرة و الصدمات النفطية السابقة، في محاولة للباحث في قراءة لأسباب حدوث الصدمة النفطية 2014، وبعدها سنحاول التعرف على مدى تأثر اقتصادات دول مجلس التعاون الخليجي ، باعتبارها من بين الدول المصدرة وذات وزن في الساحة النفطية العالمية، ونحاول في الأخير تبيان مدى انعكاسات الأزمة النفطية على أداء الأسواق المالية الخليجية، ولقد خلص البحث إلى إلا أن الانخفاض الحاد و المستمر في أسعار النفط خلال النصف الثاني من عام 2014، قد ساهم في التأثير على اتجاه أسواق الأسهم في دول مجلس التعاون الخليجي، بسبب التأثير المعنوي والسيكولوجي، ويعود إلى أن قرارات شراء أي أصول مالية وبيعها من المستثمرين الماليين، غالبا ما ترتبط بعنصر التوقعات حول أوضاع السوق المستقبلية وتغيراته. Abstract: This study, which entitled "Reflections oil shock in 2014 on the performance of the GCC stock markets", Aims to try to identify the history of the oil shocks. Through which we can compare the recent oil shock and the previous oil shocks, in a bid for the researcher to read the reasons oil shock occurred in 2014. Then we will try to identify the vulnerability of the economies of the Gulf Cooperation Council (GCC), as some of the exporting countries and the same weight in the international oil arena. We are trying in the last to show the extent of the implications of the oil crisis on the performance of the GCC financial markets. In addition, has research found that the sharp decline and continued in oil prices during the second half of 2014, it has contributed to the impact on the direction of stock markets in the Gulf Cooperation Council (GCC). Because of the moral and psychological impact, and the decisions to buy any financial assets and sale of financial investors, often associated with the element of expectations about the future and the changing of the market.
Impact of the oil shock in 2014 on the performance of the GCC stock markets
Keywords: الصدمة النفطية، دول مجلس التعاون الخليجي، أسواق الأوراق المالية الخليجية; Oil shock, The Gulf Cooperation Council, GCC stock markets